Elucidation of peptidomics, in vitro gastrointestinal digestion, and the mechanism of bioactive peptide formation in plant-based cheese alternative produced from EU PDO Malatya apricot (Prunus armeniaca L.) kernel protein and fermented with water kefir - Tekin, Ali; Ozturk, Hale Inci; Dursun, Ahmet; Fidan, Serife; Vurmaz, Melike; Sahingil, Didem; Hayaloglu, Ali Adnan (Elsevier, 2026)
This study comprehensively explores, for the first time, the effects of proteolysis and subsequent in vitro gastrointestinal system digestion on bioactive peptide dynamics in plant-based cheese alternatives (PCAs). EU PDO Malatya apricot (Prunus armeniaca L.) kernels, non-bitter taste and free of cyanogenic glycosides, were used as the protein source in the PCA production and water kefir was used to ferment the product. SDS-PAGE and RPHPLC peptide fractionation results showed that the large-molecule peptides were successfully digested, with an increase in the number of small-molecule peptides. Furthermore, fermentation promoted an increase in the counts of bioactive peptides in the PCAs, with 71 and 95 identified in control and fermented samples, respectively. Consistently, ACE-i and antioxidant activities also showed a marked increase following digestion. ACE-i activity increased from 43.98-45.49% to 90.79-92.76%, antioxidant capacities increased from 417.24-445.96 to 774.14-806.68 mg TEAC/kg for DPPH and from 0.76-1.05 to 2.79-3.10 mMol Trolox/g for CUPRAC in undigested and digested PCAs, respectively. In conclusion, the digestive capacity of apricot kernel proteins was found to be quite high, and the use of water kefir in PCA production improved the digestibility of apricot kernel proteins and increased the number of bioactive peptides.
Keywords: Cheese Analogue; Plant Protein; Proteolysis; Lc-Q-Tof-Ms; Fermentation; Seed Storage Proteins